2020
DOI: 10.1155/2020/6431314
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Capsulotomy Shape and Posterior Capsule Opacification after Low-Energy Bimanual Femtosecond Laser-Assisted Cataract Surgery

Abstract: Purpose. To evaluate capsulotomy shape and posterior capsule opacification (PCO) during an 18-month follow-up for bimanual femtosecond laser-assisted cataract surgery (FLACS). Methods. 74 eyes operated by a well-trained surgeon with bimanual FLACS technique using low-energy LDV Z8 (Ziemer Ophthalmic Systems AG, Port, Switzerland) were included in the study. The follow-up period was 18 ± 2 months. Another 91 eyes, which underwent standard bimanual microincision cataract surgery (B-MICS), served as a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…A linear dependence between EPT and corneal endothelial cell loss was described previously [33]. This trend was also further supported in a recent study where corneal endothelial cell loss was statistically significantly lower in the FLACS group, as compared to the conventional group, i.e., 288 ± 424 cells/mm 2 versus 443 ± 356 cells/mm 2 , at 18 months follow-up (p = 0.017) [34]. Other studies showed that in corneal endothelial cell loss, not only the cumulative ultrasound energy but also the irrigation/aspiration time and the amount of BSS consumed are important [35,36].…”
Section: Discussionsupporting
confidence: 79%
“…A linear dependence between EPT and corneal endothelial cell loss was described previously [33]. This trend was also further supported in a recent study where corneal endothelial cell loss was statistically significantly lower in the FLACS group, as compared to the conventional group, i.e., 288 ± 424 cells/mm 2 versus 443 ± 356 cells/mm 2 , at 18 months follow-up (p = 0.017) [34]. Other studies showed that in corneal endothelial cell loss, not only the cumulative ultrasound energy but also the irrigation/aspiration time and the amount of BSS consumed are important [35,36].…”
Section: Discussionsupporting
confidence: 79%
“…But it was observed that the FLACS group had significantly less ECC loss than conventional surgery at 1 year (8.2 vs. 11.2%). This finding is consistent with a retrospective observational study showing that the ECC loss was 12.4% and 18.1% for the low-energy FLACS vs. conventional bimanual microincision cataract surgery at 18 months post-operatively (25). The more favorable impact of FLACS on post-operative ECC change has been reported in the literature regardless of the femtosecond laser system used (1,26), suggesting the protective effects of FLACS for those who are susceptible to intraoperative and post-operative ECC loss.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Schwarzenbacher et al have demonstrated that especially low pulse energy lasers do not significantly increase the level of inflammatory cytokines (interleukin), which indicates low damage to the surrounding tissue 24 . Another article by Verdina T. et al reported, that low energy capsulotomy group had higher circularity and stability of capsulotomy diameter compared with the standard bimanual microincision cataract surgery technique over the 18-month observation period and was also associated with lower PCO rates 27 . Also, a report evaluating learning curve with the FLACS found three capsule related complications with the low energy femtosecond laser during initial 60 cases, and none after overcoming the learning curve 22 .…”
Section: Discussionmentioning
confidence: 99%